A comprehensive review of biodiesel production from waste cooking oil and its use as fuel in compression ignition engines: 3rd generation cleaner feedstock. (20th July 2021) - Singh, Digambar; Sharma, Dilip; Soni, S.L.; Inda, Chandrapal Singh; Sharma, Sumit; Sharma, Pushpendra Kumar; Jhalani, Amit
Abstract: Latest research on fuels focused on exploring better alternatives for compression ignition engines. A large number of studies reported that the properties of biodiesel are comparable with traditional diesel fuel, which makes it a suitable alternative source of energy. Among various available feedstocks, waste cooking oil is considered as the most viable source for biodiesel production. Apart from being economical, it also reduces waste disposal issues. High free fatty acids and water content in waste cooking oil cause the production of biodiesel difficult. In order to overcome this difficulty, two-step transesterification method is preferred for commercial-scale biodiesel production. Several factors like catalyst concentration, alcohol to oil molar ratio, reaction temperature, and time of reaction affect the yield of biodiesel. This article provides a comprehensive review of biodiesel production from waste cooking oil and its use in compression ignition engines. In this review, fatty acid composition, pre-treatment process, catalytic and non-catalytic approaches of biodiesel production with their advantages and limitations are included. The effect of transesterification reaction parameters on biodiesel yield is also covered. The high viscosity of biodiesel than diesel fuel causes an increase in brake specific fuel consumption and a decrease in brake thermal efficiency of engines. Significant reduction in CO, HC, PM, and smoke emissions are identified; however, NOX and CO2 emissions found increased due to the oxygenating nature of biodiesel. Overall, it could be concluded that biodiesel produced from waste cooking oil serves as a cleaner and economical alternative source of fuel for compression ignition engines. Graphical abstract: Image 1 Highlights: Approximately 30% of per capita edible oil consumption is generated as waste. Two-step transesterification is the most efficient method for biodiesel production. Yield of biodiesel is most influenced by the type of catalyst and its concentration. Brake specific fuel consumption increases due to poor atomization of biodiesel. CO, HC, PM, and smoke emissions from engine exhaust are reduced significantly.